Challenges and research priorities to progress the impact of antimicrobial stewardship - Matteo Bassetti; Daniele Roberto Giacobbe; Antonio Vena; Adrian Brink (Drugs in Context, 2019)
Antimicrobial stewardship programmes have been playing an important role in patient care and hospital policies. These programmes are now recognised as formal strategies for curbing the upward trend in antibiotic resistance and for improving the appropriate antimicrobial and antifungal use. The role of such programs in the era of antimicrobial resistance presents several unique challenges and opportunities, most notably in the diagnostic and therapeutic setting. Controversies remain regarding the most effective interventions and the appropriate design to evaluate their impact. In this review, based on rounds of discussion, we explain the most important challenges faced by antibiotic stewardship and antifungal stewardship programmes. We also try to suggest areas for further research.